The conditional relationship between beta and stock returns: An empirical study in the Colombo Stock Market - Riyath, M.I.M.; Jahfer, Athambawa (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
The objective of this research is to find out the conditional relationship between beta and stock returns for the period 1999 to 2013 in the Sri Lankan market. This study tests whether the beta factor has an ability to influence on the stock returns and attempts to investigate the conditional relationship between beta and stock returns in Sri Lanka. This study reveals that the relationship between beta- return is positive during the up market condition and the relationship is negative during the down market condition in Colombo Stock Exchange during the study period. Therefore, the beta-realized return relationship is hold in the Colombo Stock Exchange with market condition such as up and down markets.
Keywords: CAPM; Beta; Stock return; Colombo stock exchange